2024
DOI: 10.1186/s40658-024-00628-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation of image-derived input function using a long axial field of view PET/CT scanner for two different tracers

Xavier Palard-Novello,
Denise Visser,
Nelleke Tolboom
et al.

Abstract: Background Accurate image-derived input function (IDIF) from highly sensitive large axial field of view (LAFOV) PET/CT scanners could avoid the need of invasive blood sampling for kinetic modelling. The aim is to validate the use of IDIF for two kinds of tracers, 3 different IDIF locations and 9 different reconstruction settings. Methods Eight [18F]FDG and 10 [18F]DPA-714 scans were acquired respectively during 70 and 60 min on the Vision Quadra PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Despite their potential, graphical methods have been shown to be potentially susceptible to bias [30], primarily influenced by the accuracy of estimating the later segments of the input functions. Incorporating blood samples for scaling scanner, has demonstrated that that accuracy of IDIF from larger blood pools varies depending on the tracer applied, necessitating validation for each tracer [31]. Our study contributes to these efforts by corroborating their conclusions regarding the highly accurate IDIF extraction of [ 18 F]FDG purposes can greatly improve the accuracy of the IDIF curves' tail [30].…”
Section: Discussionsupporting
confidence: 63%
“…Despite their potential, graphical methods have been shown to be potentially susceptible to bias [30], primarily influenced by the accuracy of estimating the later segments of the input functions. Incorporating blood samples for scaling scanner, has demonstrated that that accuracy of IDIF from larger blood pools varies depending on the tracer applied, necessitating validation for each tracer [31]. Our study contributes to these efforts by corroborating their conclusions regarding the highly accurate IDIF extraction of [ 18 F]FDG purposes can greatly improve the accuracy of the IDIF curves' tail [30].…”
Section: Discussionsupporting
confidence: 63%